Pertumbuhan Gross dan Net Populasi Ternak Sapi di Sulawesi Selatan - Paly, Basir (Jurusan Biologi UIN Alauddin Makassar, 2013)
This research aims to know the Gross and the Net population growth of beef cattle the last 5 years (2009-2013) in South Sulawesi. Implemented in four regency, namely, Gowa, Bone, Barru and Enrekang. Site selection was based on the consideration that the four regency are the areas of the development of cattle with a total population of about 45.26% of the total population who are of South Sulawesi. Type of this research is quantitative survey method. The population of the research was the whole group/cattle farmers in four areas. Then each regency selected four groups as the sample, so that the number of samples that are observed as many as 16 groups. Data collection was done through observation and interviews by using the questionnaire. The observed variables are; (1) the number and type of livestock owned, (2) the number of males and females, (3) the addition of the parent, males and famales from outside the province, (4) sales, cut withholding, and cases of death, and (5) the number of births. The results showed that over the last five years (2009-2013) Gross population growth of beef cattle in South Sulawesi 11.46% per year, growth above the national average of 10.26% per year. While the growth of the Net population average at 11.18% per year, whereas the Net population smaller (11: 18 < 11.46) from the Gross population. Its main cause is the amount of sales, cut withholding, and cases of death which is not compare with birth rate.Keywords: gross, growth, net, population